Politically Driven: Mapping Political and Media Discourses of Penal Populism—The Hungarian Case. (November 2015) - Boda, Zsolt; Szabó, Gabriella; Bartha, Attila; Medve-Bálint, Gergő; Vidra, Zsuzsanna
Penal populism, advocating severe punishment of criminals, has greatly influenced justice policy measures in Eastern Europe over the last decade. This article takes Hungary as a typical case in the region and based on a recent criminal policy reform it investigates the roots of the penal populist discourse, which legitimizes and supports punitive measures. The research assumes that policy discourses need specific social actors that construct and promote them. Accordingly, the article explores whether the right-wing political parties and the tabloid media have taken a leading role in constructing the discourse of penal populism as a response to public concerns about crime. Content analysis and frame analysis of political communication and media was conducted to identify the discursive positions of major political parties and selected national media sources. The research found that penal populism was dominant in Hungarian political discourse while most of the media, including the tabloid press, have been rather reluctant to adopt punitive tones. The results thus contradict previous findings and offer a more nuanced view on how penal populism is being constructed and promoted in Eastern Europe.